EFESIENSI USAHA PENGOLAHAN KOPI DENGAN BEBERAPA METODE (STUDI KASUS PADA USAHA KOPI DADONG) - Wijaya, Bagus Reynaldy; Martiningsih, Ni Gst. Ag. Gde Eka; Suparyana, Pande Komang (Fakultas Pertanian Universitas Mahasaraswati Denpasar, 2019)
The objectives of this study are: Identifying the results of quality coffee processing with full washed, natural and honey methods, Analyzing the cost, revenue, and income of coffee processing business with full washed, natural and honey methods, and Analyzing the level of efficiency of coffee processing business with full washed, natural and honey methods at the Kopi Dadong business in Belantih Village.The respondents in this study were the owner of dadong coffee business in Belantih Village. This research using descriptive and efficiency analysis.The results showed that Green bean with a process of full washed, natural and honey was in the category of Quality 1. The total costs incurred at the Dadong Coffee business in Belantih Village for processing of full washed, natural and honey respectively Rp.134.967.111, -, Rp.116.834.861, - and Rp.132.717.111, -. Receipts generated on Dadong Coffee business in Belantih Village for processing of full washed, natural and honey in a row is Rp.171.000.000,-, Rp.180.800.000,- and Rp.171.000.000,-. The income from the Dadong Coffee business in Belantih Village for processing of full washed, natural and honey in a row is Rp.36.032.889, -, Rp.63.965.139,- and Rp.38.282.889,-. Dadong Coffee Business in Belantih Village with processing of full washed, natural and honey is efficient and profitable to run. This can be seen from the value of efficiency greater than 1. Efficiency value of the business of Dadong Coffee in Belantih Village for processing of full washed, natural and honey in succession 1.27, 1.55, 1.29.